Wireless walker dynamometer design and static calibration based on ant colony system. Issue 3 (1st September 2013) - Xu, Rui; Ming, Dong; Qiu, Shuang; Wang, Xin; Qi, Hongzhi; Zhang, Lixin; Wan, Baikun
Abstract : Walker is a widely used mobility aid to improve users' stability and ambulatory ability. Its dynamometer instrumentation is necessary for quantitative study of basic biomechanics and functional requirements for effective use. How to extract the kinetic demands exactly and without any disturbance to normal gait remains a bottleneck for walker dynamometer design. Based on the force measurement of handle reaction vectors (HRVs) applied to the walker, this study developed a novel strain gauge‐based wireless walker dynamometer system integrated with a static calibration algorithm based on ant colony system (ACS). Compared with the traditional measurement of HRV, the proposed method enhances security and flexibility of walker use by using one wireless data transmission system connecting 12 strain‐gauge bridges mounted on the walker frame with the computer. To improve high‐dimensional calibration performance, an ACS algorithm was employed to optimise the sensitivity weight matrix during calibration. To evaluate force measurement reliability, system performance with ACS algorithm was testified and its mean non‐linearity, mean crosstalk and maximal force measurement accuracy error were found to be 6.88, 6.10 and 7.46%, respectively, which were much better than those of traditional linear calibration methods. This implemented walker dynamometer system may prove to be a reliable tool for measurement of hand loads and description of kinetic analysis of basic walker‐assisted gait.